ETOS KERJA ISLAMI DALAM MEWUJUDKAN KESEJAHTERAAN SOSIAL - Mia Fitriah Elkarimah (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2016)
Indicators of human quality is a human who has a high work ethic, human quality means certainly have high motivation, always work and achievement. The quality of human resources is a central point of movers and managers from various types of other resources. The work ethic in Islam perspective is not enough to get the one purpose of welfare, but a manifestation of pious charity whose purpose is more comprehensive, Islam assess welfare Â must be guided with other instruments such as charity, donation, and shadaqah. The fact, Muslim has not been fully implemented yet the instrument. For this reason will be explained relation work ethic and social welfare in Islam perspective as a mediator to contact among segments